A new species of Corydalus Latreille, 1802 (Megaloptera, Corydalidae) and first record of C. clavijoi Contreras-Ramos, 2002 and C. nubilus Erichson, 1848 from Colombia - Ardila-Camacho, Adrian (Zootaxa, 2014)
A new species of the dobsonfly genus Corydalus from the Colombian Andean region is described and illustrated. This species is unique in having the longest tenth gonostyli of all known species of the genus and is apparently closely related to members of the C. nubilus group. In addition, C. clavijoi Contreras-Ramos and C. nubilus Erichson are recorded for the first time from Colombia and new Colombian locality records are provided for other known species. A key to Colombian species of Corydalus is included.